Scandium and titanium containing single-walled carbon nanotubes for hydrogen storage: A thermodynamic and first principle calculation - Mananghaya, Michael (Animo Repository, 2016)
The generalized gradient approximation (GGA) to density functional theory (DFT) calculations indicate that the highly localized states derived from the defects of nitrogen doped carbon nanotube with divacancy (4ND-CNxNT) contribute to strong Sc and Ti bindings, which prevent metal aggregation. Comparison of the H2 adsorption capability of Sc over Ti-decorated 4ND-CNxNT shows that Ti cannot be used for reversible H2 storage due to its inherent high adsorption energy. The Sc/4ND-CNxNT possesses favorable adsorption and consecutive adsorption energy at the local-density approximation (LDA) and GGA level. Molecular dynamics (MD) study confirmed that the interaction between molecular hydrogen and 4ND-CNxNT decorated with scandium is indeed favorable. Simulations indicate that the total amount of adsorption is directly related to the operating temperature and pressure. The number of absorbed hydrogen molecules almost logarithmically increases as the pressure increases at a given temperature. The total excess adsorption of hydrogen on the (Sc/4ND) 10 -CNxNT arrays at 300 K is within the range set by the department of energy (DOE) with a value of at least 5.85 wt%.